A Bibliometric Analysis of Nano Metal-Organic Frameworks Synthesis Research in Medical Science Using VOSviewer - Andika Purnama Shidiq (Universitas Pendidikan Indonesia (UPI), 2023)
Nano MOFs (nMOFs) have now evolved as a new class of MOF with exciting applications. The purpose of this research is to perform bibliometric analysis on nMOFs for medical science by combining mapping analysis using VOSviewer software. Application reference manager used to obtain research data. The data obtained is the result of a search based on the keyword